2005
DOI: 10.1080/00207450590897941
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal complaints among a group of Turkish nurses

Abstract: The aim of the present study was to describe the prevalence and distribution of symptoms of musculoskeletal complaints among Turkish nurses who are practicing general nursing. The study population consisted of 120 nursing staff from four large general hospitals in Erzurum, Turkey. In every hospital six departments (surgery, medical, obstetric and gynecology, psychiatry, pediatric, and neurology) were selected. A Nordic standardized questionnaire described by Kuorinka et al. (1987) about complaints of the muscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
32
2
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 27 publications
11
32
2
16
Order By: Relevance
“…As abovementioned in table 1 the results of neck pain severity in terms of working departments in last month in this study between 15 September and 15 October 2012 is to some extent in agreement with a study was done in Turkey among the nurses, to determine the prevalence rates and the risk factors of WMSDs of low back, shoulder and neck complaints, and the results have showed that and the nurses who were working in the departments of general surgery and obstetrics & gynecology had more WMSDs complaints than the nurses in other departments 10 . Also neck pain disability have assessed through neck pain interfering with daily work activities according to study in Belgium 3 ,and in this study the respondents have reported that neck pain interfered with their activities from minimum one day to maximum three weeks, on average one neck pain have interfered them about 7 days in doing their daily work activities during working hours, regardless the working departments.…”
Section: Neck Pain Severitysupporting
confidence: 72%
“…As abovementioned in table 1 the results of neck pain severity in terms of working departments in last month in this study between 15 September and 15 October 2012 is to some extent in agreement with a study was done in Turkey among the nurses, to determine the prevalence rates and the risk factors of WMSDs of low back, shoulder and neck complaints, and the results have showed that and the nurses who were working in the departments of general surgery and obstetrics & gynecology had more WMSDs complaints than the nurses in other departments 10 . Also neck pain disability have assessed through neck pain interfering with daily work activities according to study in Belgium 3 ,and in this study the respondents have reported that neck pain interfered with their activities from minimum one day to maximum three weeks, on average one neck pain have interfered them about 7 days in doing their daily work activities during working hours, regardless the working departments.…”
Section: Neck Pain Severitysupporting
confidence: 72%
“…[10][11][12][13] Despite the high incidence of WRMD worldwide, most epidemiological investigations among nurses have been restricted to high-income countries, and only one study with a small group has been conducted in Turkey. 14 Given that there are 71600 nurses currently working in Turkey, 15 we believe it is necessary to investigate WRMD in a larger group of nurses. Therefore, this study aims to investigate the prevalence of WRMD and the associated risk factors among Turkish hospital nurses and to compare the findings with the results of studies conducted in other countries.…”
mentioning
confidence: 99%
“…17 Other studies with similar findings showing high incidence of musculoskeletal hazards among health care workers included. [18][19][20] Another important finding was occupational health hazards related to blood borne disease, this is in line with study on perception and prevalence of work-related health hazards among health care workers in public health facilities in southern India. The study showed result that among the 81.5% who reported exposure to biological hazard, 93.9% had direct skin contact with infectious materials.…”
Section: Discussionmentioning
confidence: 52%